Ferulic acid inhibits advanced glycation end products (AGEs) formation and mitigates the AGEs-induced inflammatory response in HUVEC cells. (September 2018) - Liu, Jian-li; He, Yong-lin; Wang, Shuai; He, Yin; Wang, Wei-yu; Li, Qi-jiu; Cao, Xiang-yu
Graphical abstract: Ferulic acid inhibits the formation of advanced glycation end products (AGEs) and mitigates the AGEs-induced inflammatory response in HUVEC cells by suppressing the activation of NF-κB and p38 MAPK signaling pathway. Highlights: Ferulic acid inhibited the Advanced glycation end products (AGEs) formation in vitro. Ferulic acid inhibited the AGEs-induced inflammatory response. Ferulic acid inhibited AGEs-mediated the activation of p38 MAPK and NF-κB signaling pathways. Abstract: Advanced glycation end products (AGEs) are complex and heterogeneous compounds, which play an important role in diabetic-related vascular complications, especially in atherosclerosis. In this study, the effects of ferulic acid (FA) on glucose-related protein glycation were investigated in vitro by various spectroscopic techniques and molecular docking methods. In order to study the protective effects of FA on AGEs-induced HUVEC cells damage, the mRNA expression of Caspase-1, NLRP3, CRP, ICAM-1, VCAM-1, IL-18 and IL-1β were detected. Moreover, NF-κB and p38 MAPK signaling pathways were analyzed. These results manifested that FA could effectively inhibit the AGEs formation, decrease the AGEs-induced mRNA expression of Caspase-1, NLRP3, CRP, ICAM-1, VCAM-1, IL-18 and IL-1β, and reduce intracellular ROS. FA could mitigate the AGEs-induced inflammatory response in HUVEC cells by suppressing the activation of NF-κB and p38 MAPK signaling pathways. These results suggested that FA might prevent and mitigate the development of atherosclerosis in diabetic patients.